Assessment of rainfall monitoring network in state of Pará (Research, Society and Development, 2020)
A pluviometric network is formed by an organized set of stations, spatially distributed with technical criteria and recommendations such as density, to operate more efficiently. In regions such as the Amazon, the implementation of these monitoring networks faces several difficulties, due to the fact that there are not enough stations to serve its great territorial extension and many of the existing ones are deactivated, as well as many that present data with failures or points with observation period of very short. Therefore, this work aims to analyze an existing rainfall monitoring network in the State of Pará, located in the northern region of Brazil. For this, criteria such as density and spatial distribution of active and inactive rainfall stations in each Pará region will be observed, based on the recommendations of the World Meteorological Organization (WMO). It was observed that, in general, the existing stations in the state of Pará do not show homogeneity in their spatial distribution. The rainfall network in Pará has 380 stations of wich 27, 11% are deactivated. In addition, based on the total number of stations found, a percentage of 25% has no data available and only 26% has data series with 30 years or more. From this, it can be proved that most stations have a short period of data, which ends up making it difficult to carry out studies that use it as a source for analyzing longer series of historical series in the region.